Analysis of Ethical Leadership In Forming Employee Work Behavior at PT. BDE - Hikmat, Hikmat; Salam, Rahmat (Jurnal Ilmiah Sumber Daya Manusia, 2024)
The study seeks to ascertain and evaluate Ethical Leadership in Shaping Employee Work Behavior at PT. BDE. The study's research approach is a descriptive qualitative method, through interviews and observations with the research object, namely the employees of PT. BDE . The findings from the study and debate are 1. Ethical leadership applied by PT BDE in its employees is a) creating the right values and morals in the workplace, b) shaping the way an employee carries out their work duties with high moral standards , c) fostering loyalty, discipline, order, neatness and creating employees who have attitude. 2. Employee Work Behavior at PT. BDE is already quite good, namely working well and being responsible, outgoing and hardworking. However, it has both positive and negative types of behavior.